IMPORTANCE OF HR LEARNING AND DEVELOPMENT ACTIVITIES FOR SMES (International Journal of Food and Nutritional Sciences, 2023)
Introduction: The main agenda of this research is to address the importance of theHR training and development within an SMEs. This study helps to gain knowledgeOf HR collaboration and its facilities to develop the performance of the organization.Literature Review: As per the review, it has been identified HR training help to boost team moral value to improve the skills and competencies for relevant jobs responsibility.Methodology: This research is based on the primary method, selected “quantitative research process”. The primary research strategy collects authenticated data from participants of the specific group. This research method quantifies the responded in a statistical way.Findings: This research uses “SPSS Software” to analyze the collected data quantitatively. Therefore, with the aid of this software, statistical data regarding HR development and training activity process has been process successfully. Therefore, based on 3 demographic and 7 statistical questions, which is able to collect data from online survey methods.Discussion: From the above findings, it can be stated that training and development opportunity in the workplace is a vital aspect of ensuring SMEs performance standard and HR team embrace open communication and collaboration for low team conflicts.Conclusion: Overall research topic has been discussed in this section to gain in-depth knowledge regarding HR training and development program.